Disparities in home health service providers among Medicare beneficiaries with stroke. Issue 1 (2nd January 2016) - Iyer, Medha; Bhavsar, Grishma P.; Bennett, Kevin J.; Probst, Janice C.
ABSTRACT: This study examined the intensity of home health services, as defined by the number of visits and service delivery by rehabilitation specialists, among Medicare beneficiaries with stroke. A cross-sectional secondary data analysis was conducted using 2009 home health claims data obtained from the Centers for Medicare and Medicaid Services' Research Data Assistance Center. There were no significant rural-urban differences in the number of home health visits. Rural beneficiaries were significantly less likely than urban beneficiaries to receive services from rehabilitation specialists. Current home health payment reform recommendations may have unintended consequences for rural home health beneficiaries who need therapy services.